A Group Contingency Plus Self-Management Intervention Targeting At-Risk Secondary Students' Class-Work and Active Engagement. (November 2015) - Trevino-Maack, Sylvia I.; Kamps, Debra; Wills, Howard
The purpose of the present study is to show that an independent group contingency (GC) combined with self-management strategies and randomized-reinforcer components can increase the amount of written work and active classroom responding in high school students. Three remedial reading classes and a total of 15 students participated in this study. Students used self-management strategies during independent reading time to increase the amount of writing in their reading logs. They used self-monitoring strategies to record whether or not they performed expected behaviors in class. A token economy using points and tickets was included in the GC to provide positive reinforcement for target responses. The results were analyzed through visual inspection of graphs and effect size computations and showed that the intervention increased the total amount of written words in the students' reading logs and overall classroom and individual student academic engagement.